PENGARUH KUALITAS LAYANAN DAN SUASANA TOKO TERHADAP KEPUASAN PELANGGAN (Studi Kasus Pada PO. Binter 88 Travel Kota Bengkulu) - Febri Andrian Putra; Subandrio Subandrio (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2023)
Based on data analysis using SPSS 26, the multiple linear regression equation is as follows: Y = 1.634 + 0.565x1+0.221x2 + e Value. The correlation coefficient above shows if the correlation coefficient interval is at 0.799 - 0.1000 Service Quality (X) and Store Atmosphere (X2) has a strong influence on Customer Satisfaction (Y). Coefficient of Multiple Determination (R Squere) R2 = 0.591 or (59%) where the value of the coefficient of multiple determination means that together Service Quality (X1) and Store Atmosphere (X2) contribute to influencing Customer Satisfaction (Y) at Po . Binter 88 Travel Bengkulu City by 59% % while the remaining 41% is influenced by other factors outside the study. Known the value of t test Sig. for the effect of Service Quality (X1) on Customer Satisfaction (Y) is 0.000> 0.005 and the t-count value is 9.499>1.984 t table. so it can be concluded that there is a significant influence between the variables of Service Quality (X1) on Customer Satisfaction (Y). Given the value of Sig. for the effect of Store Atmosphere (X2) on Customer Satisfaction (Y) is 0.004 > 0.005 and the t-count value is 2.963 > 1.984 t table. so that it can be concluded that there is a significant effect between Product Quality (X2) variables on Purchase Interest (Y). it can be seen that the results of the F test are f = 68,620 with a significance of 0.000 while the f table is f = 3.938 with a significance of 0.05. From the information above, f arithmetic > f table can be stated Ho is rejected and Ha is accepted, and it can be concluded that simultaneously there is an effect of Service Quality (X1), and Store Atmosphere (X2) on Customer Satisfaction (Y). Keywords: Service Quality, Store Atmosphere And Customer Satisfaction